2005
DOI: 10.1074/jbc.m500163200
|View full text |Cite
|
Sign up to set email alerts
|

Lower Inhibitor Development in Hemophilia A Mice following Administration of Recombinant Factor VIII-O-Phospho-L-serine Complex

Abstract: Factor VIII is a multidomain protein composed of A1, A2, B, A3, C1, and C2 domains. Deficiency or dysfunction of factor VIII causes hemophilia A, a bleeding disorder. Administration of exogenous recombinant factor VIII as a replacement leads to development of inhibitory antibodies against factor VIII in 15-30% of hemophilia A patients. Hence, less immunogenic preparations of factor VIII are highly desirable. Inhibitory antibodies against factor VIII are mainly directed against immunodominant epitopes in C2, A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 46 publications
2
70
0
Order By: Relevance
“…Plasma was separated by centrifugation at 5,000×g at 4°C for 5 min. Previous studies have shown that 6 weeks is an appropriate time to compare antibody titers between various treatment groups (27). Samples were stored at −80°C immediately after centrifugation until analysis.…”
Section: In Vivo Characterization Of Fviii-pimentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma was separated by centrifugation at 5,000×g at 4°C for 5 min. Previous studies have shown that 6 weeks is an appropriate time to compare antibody titers between various treatment groups (27). Samples were stored at −80°C immediately after centrifugation until analysis.…”
Section: In Vivo Characterization Of Fviii-pimentioning
confidence: 99%
“…Inhibitory antibody titers were measured by the Nijmegen modification of the Bethesda assay (27,41). This assay is a modification of the one-stage aPTT assay which measures the ability of FVIII antibodies to inhibit the biological activity of FVIII.…”
Section: Measurement Of Inhibitory Anti-fviii Antibody Titersmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma was collected as before and stored immediately at −80°C. Inhibitory antibody titers were measured by the Nijmegen modification of the Bethesda assay (38,39). Clotting times determined from various dilutions (1:2 to 1:1,024) of normal coagulation control plasma were used to create a calibration curve.…”
Section: Immunogenicity Studiesmentioning
confidence: 99%
“…It has been established that the presentation of an antigen to dendritic cells in a tolerogenic manner can promote peripheral tolerance via induction of regulatory T cells (32). We have shown that administration of therapeutic proteins such as FVIII in the presence of an immune-modulatory lipid phosphatidyl serine (PS) reduces development of inhibitory antibody responses against FVIII and promotes a hyporesponsiveness by tolerogenic presentation to dendritic cells (33)(34)(35)(36). As the preexposure of FVIII in the presence of PS induced tolerance/hyporesponsiveness, we proposed a novel strategy called reverse vaccination to induce tolerance and thereby reduce immunogenicity of therapeutic proteins given sc.…”
Section: Strategies To Mitigate Immunogenicitymentioning
confidence: 99%